Challenges of the Social Function of a Mediator at a Particular Stage of Mediation and Personal Spirit beyond the Scope of Mediated Agreement - Leonidze, Irakli (Alternative Dispute Resolution Yearbook, 2020)
Annotation is available in Georgian